2007
DOI: 10.1063/1.2437675
|View full text |Cite
|
Sign up to set email alerts
|

Underwater streamer propagation analyzed from detailed measurements of pressure release

Abstract: In this paper we describe experimental observations connected with the propagation of primary and secondary streamers in water. Using a Mach-Zehnder interferometer we determined the pressure field surrounding the streamer channel at a given instant in time with high temporal and spatial resolution. This pressure field contains information on the time evolution of the pressure pulse inside the discharge channel. The pressure history in the channel has been reconstructed by comparing the experimentally obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
146
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 29 publications
17
146
2
Order By: Relevance
“…The discharge observed here is different from the discharge produced by microsecond or sub-microsecond duration pulses from aforementioned publications. [5][6][7] In our case, the discharge demonstrated a more spherical shape with a few major branches, while the microsecond or submicrosecond discharges usually have a complicated bush-like structure. The propagation of the nanosecond discharge reached about 1000 km/s, which was two orders of magnitude higher than the velocity observed in low density plasma filaments.…”
Section: Experiments Setupmentioning
confidence: 98%
See 1 more Smart Citation
“…The discharge observed here is different from the discharge produced by microsecond or sub-microsecond duration pulses from aforementioned publications. [5][6][7] In our case, the discharge demonstrated a more spherical shape with a few major branches, while the microsecond or submicrosecond discharges usually have a complicated bush-like structure. The propagation of the nanosecond discharge reached about 1000 km/s, which was two orders of magnitude higher than the velocity observed in low density plasma filaments.…”
Section: Experiments Setupmentioning
confidence: 98%
“…[5][6][7] For example, An et al 7 demonstrated that with 40-ns rise time and 10-μs duration time, the development velocity of the discharge is a Author to whom correspondence should be addressed. To answer these questions, a nanosecond pulsed power system (with pulse duration about 10 ns) synchronized with a picosecond ICCD camera (with minimum gate time 50 ps) was used to study the time-resolved evolution of nanosecond discharge in water.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, pressure, temperature and gas composition vary from one phenomenon to the next. In electrical engineering, the higher densities of liquids are desirable for fast switching, but pre-existing microbubbles largely influence streamer properties in fluids [13,14]. For this reason, the operation of spark gaps filled with supercritical fluids is now under investigation [15].…”
Section: Streamers In Different Media At Various Densitiesmentioning
confidence: 99%
“…12,17,19 Underwater streamer discharges at positive polarity also have two propagation modes: a primary streamer and a secondary streamer. [20][21][22][23][24][25][26][27] The primary streamer appears at lower applied voltage with a propagation velocity of 2-3 km/s, having a semi-spherical brush-like structure ($500 lm) composed of many filaments. 22,26 All but a few filaments disappear within 400 ns, resulting in a tree-like structure.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] The primary streamer appears at lower applied voltage with a propagation velocity of 2-3 km/s, having a semi-spherical brush-like structure ($500 lm) composed of many filaments. 22,26 All but a few filaments disappear within 400 ns, resulting in a tree-like structure. 26 The primary streamer propagates during the flow of repetitive pulsed currents.…”
mentioning
confidence: 99%